2002
DOI: 10.1016/s0022-2275(20)30158-9
|View full text |Cite
|
Sign up to set email alerts
|

UV analysis of Amadori-glycated phosphatidylethanolamine in foods and biological samples

Abstract: Maillard reactions are among the most important of the chemical and oxidative changes occurring in food and biological samples that contribute to food deterioration and to the pathophysiology of human disease. Although the association of lipid glycation with this process has recently been shown, the number of lipid glycation products in food and biological materials has not been clear. In this study, we synthesized the Amadori products derived from the glycation of phosphatidylethanolamine (PE), i.e., Amadori-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The synthesis efficiency of glycated PE was determined by HPLC-MS/MS to be greater than 50% for both GPE and LPE. These results are consistent with previous studies conducted in our laboratory [11,12]. On the other hand, liposomes containing glycated PE were found to exhibit a significant reduction in negative zeta potential, compared with liposomes containing non-glycated PE (figure 4c).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The synthesis efficiency of glycated PE was determined by HPLC-MS/MS to be greater than 50% for both GPE and LPE. These results are consistent with previous studies conducted in our laboratory [11,12]. On the other hand, liposomes containing glycated PE were found to exhibit a significant reduction in negative zeta potential, compared with liposomes containing non-glycated PE (figure 4c).…”
Section: Discussionsupporting
confidence: 93%
“…Glycated PE was prepared according to the method previously described by Miyazawa et al [11,12]. In this glycation reaction, the amino group of PE and the hydroxyl group of the saccharide react via a dehydration condensation reaction to form an unstable ring-opening compound known as a Schiff base (-C = N-).…”
Section: Preparation Of Glycated Phosphatidylethanolaminementioning
confidence: 99%
See 1 more Smart Citation
“…Together with PC, PS, PI, PE represents the backbone of most biological membranes. Phosphoethanolamines in food break down to form phosphoethanolamine-linked amadori products, which act as a part of the Maillard reaction [ 36 ]. These products accelerate membrane lipid peroxidation and cause oxidative stress on cells exposed to them [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“… 4–11 To date, Amadori-glycated phosphatidylethanolamine (Amadori-PE) has been detected in a number of foodstuffs. 8,12 Oak et al examined Amadori-PE presence in several food samples, among which infant formula, chocolate, mayonnaise and soybean milk, found to contain a high amount of Amadori-PE. 8 Utzmann et al found PE-linked glycated products in model systems as well as in spray-dried egg yolk.…”
Section: Introductionmentioning
confidence: 99%